2013
DOI: 10.7575/ijalel.v.2n.1p.186
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Attitude on L2 Learners’ Choice of Compensation & Meta-cognitive Strategies

Abstract: The present study investigates the effect of attitude on the choice of compensation and meta-cognitive strategies of Iranian EFL university students majoring in Teaching English and English Translation. 108 intermediate students from Qazvin and Takestan State and Islamic Azad Universities participated in this study. Data were gathered by means of questionnaires and were analyzed using ANOVA procedures. Results indicated that the level of attitude had a statistically significant effect on the choice of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…When the relative importance of extrinsic and intrinsic motivation was investigated (Ziaosseini & Salahi, 2008), intrinsic motivation was found to correlate significantly with the choice of language learning strategies, while extrinsic motivation was not. In terms of the correlation between motivation and learning strategy types, Zarei and Elekaei (2013) found that students' learning motivation levels influenced the use of memory, compensation, and practical strategies. However, they did not influence cognitive, metacognitive, and social strategies.…”
Section: Discussionmentioning
confidence: 99%
“…When the relative importance of extrinsic and intrinsic motivation was investigated (Ziaosseini & Salahi, 2008), intrinsic motivation was found to correlate significantly with the choice of language learning strategies, while extrinsic motivation was not. In terms of the correlation between motivation and learning strategy types, Zarei and Elekaei (2013) found that students' learning motivation levels influenced the use of memory, compensation, and practical strategies. However, they did not influence cognitive, metacognitive, and social strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Istraživanje koje je obuhvatalo učenike na početnom nivou učenja engleskog jezika u Iranu pokazuje da oni koriste razne vrste kompenzatornih strategija kako bi preneli poruku prilikom govorne produkcije (Karbalaei & Taji, 2014). Zarei i Elekaei (Zarei & Elekaei, 2013) istražuju uticaj stava na izbor kompenzatornih i metakognitivnih strategija, sa zaključkom da stav iranskih studenata koji uče engleski jezik kao strani u znatnoj meri utiče na izbor kompenzatornih strategija.…”
Section: Pregled Rezultata Dosadašnjih Istraživanjaunclassified
“…Similarly, Zarei and Elekaei (2013) investigated the effect of attitude on the choice of compensation and meta-cognitive strategies of compEnsation stratEGiEs…”
Section: Hong-nam and Leavellmentioning
confidence: 99%
“…Commonly, they use compensation strategies, which enhance their accomplishment. For example, students simply refrain from conversation or topics for which they have no adequate vocabulary knowledge; they switch to their first language or ask for help (Moattarian & Tahririan, 2013;Pazhakh, 2007;Tajeddin & Alemi, 2010;Zarei & Elekaei, 2013;). …”
Section: Introductionmentioning
confidence: 99%